Effects of controlled atmosphere storage on some chemical properties of bananas (Musa sapientum var. Lacatan) - Runez, Mercedes Moran
Bananaof the var. Lacatan were subjected to varying levels of CO2 and O2 (0.6-1.7, 2.6-3.0, 3.4-3.5,6.1-1.2, 6.8-1.7, 8.4-1.5) for a period of 21 days at 61°F. Two controls - room (81.7°F) and refrigerator (61°F) packed in perforated polyethylene bags served as bases for comparison. Chemical tests (pH, % soluble solids, % titrable acidity and % reducing and non-reducing sugars) were done on the controls and the treated samples. Objective and subjective tests showed no significant differences among all treatments. Under conditions of this experiment, therefore, controlled atmosphere has proven advantageous in that there was delay in ripening of the fruits with no significant effects on the chemical and organoleptic properties of the bananas.